Matematyka
rusus505800498
2017-06-23 18:57:17
Rozwiąż równania proszę o pomoc
Odpowiedź
Daniel2043
2017-06-23 23:29:51

b)(2x+1)²=(4x+5)² 4x²+4x+1=16x²+40x+25 4x²-16x²+4x-40x+1-25=0 -12x²-36x-24=0/:12 -x²-3x-2=0 Δ=b²-4ac Δ=9-4*(-1)*(-2) Δ=9-8 Δ=1         √Δ=1 x1=(-b-√Δ)/2a                          x2=(-b+√Δ)/2a x1=(3-1)/2*(-1)                         x2=(3+1)/2*(-1) x1=2/-2                                    x2=4/-2  x1=-1                                       x2=-2    d) f(x)=x²-5x/2  +3    x-5x/2 +3 =0 Δ=(5/2)²-4*1*3 Δ=25/4 -12 Δ=-23/4 Δ=-5 3/4  Δ<0 brak rozwiązania

marijka
2017-06-23 23:31:06

[latex]b)\(2x+1)^2=(4x+5)^2\\(2x)^2+2*2x*1+1^2=(4x)^2+2*4x*5+5^2\\4x^2+4x+1=16x^2+40x+25\\4x^2-16x^2+4x-40x+1-25=0\\-12x^2-36x-24=0 /:12\\-x^2-3x-2=0\\a=-1\\b=-3\\c=-2\\Delta=b^2-4ac\\Delta=(-3)^2-4*(-1)*(-2)=9-8=1\\ sqrt{Delta} = sqrt{1} =1\\x_1= frac{-b- sqrt{Delta} }{2a}\\x_1= frac{-(-3)-1}{2*(-1)} = frac{3-1}{-2} = frac{2}{-2}=-1\\ x_2= frac{-b+ sqrt{Delta} }{2a}\\x_2= frac{-(-3)+1}{2*(-1)} = frac{3+1}{-2} = frac{4}{-2}=-2[/latex] d) [latex]f(x)=x^2- frac{5}{2}x+3\\ x^2- frac{5}{2}x+3=0 /*2\\2x^2- frac{10}{2} x+6=0\\2x^2-5x+6=0\\a=2\\b=-5\\c=6\\Delta=b^2-4ac\\Delta=(-5)^2-4*2*6=25-48=-23\\Delta=-23\\Delta extless 0[/latex] Jeżeli [latex]Delta extless 0[/latex] brak rozwiązania.

Dodaj swoją odpowiedź